Space-structural modelling of concepts, reflecting attitudes towards the professions in the textile industry - Suslavičius , A.; Rubaževičienė , M. (Psichologija, 1985)
The technique of semantic differential by Ch. Osgood was used for the measurement of attitudes towards the professions in the textile industry. Apart from the quantitative treatment of data obtained by using this technique there is also a possibility of its qualitative treatment, i. e. spatial representation of the studied concepts, reflecting certain attitudes. Thus is achieved a better understanding of how these notions are clustered and what their spatial arrangement is. The subjects were pupils from a vocational-technical school. They were given 12 concepts, reflecting the essential professions in the textile industry, with the purpose of their subsequent evaluation. The results of the investigation enabled us to establish the hierarchy of professions. The establishment of linear distances in semantic space (D) formed a notion of how these attitudes are spatially situated. The numerical values of the distances between professions were expressed graphically in a three-vector space. The spatial representation of attitudes permitted us to establish their clusters, and also the degree of identification of a subject with a certain profession.